Unified solution of non-limit active and passive earth pressure of retaining wall considering soil arching effect - Guihai Gao; Jianxu Chen; Bo Qian; Mei Xiong (PLoS ONE, 2025)
The existing theory can not get the unified solution of non-limit active and passive earth pressure with clear mechanical concept. Based on Duncan-Chang stress-strain model, this paper puts forward a relationship between friction angle and wall displacement ratio, which can consider both non-limit active state and non-limit passive state. According to the horizontal layer analysis method, the unified solution of non-limit active and passive earth pressure of retaining wall can be derived, which can be reduced to Rankine solution. The feasibility of the formula is verified by comparing the research results of this paper with the existing theoretical and experimental values. It is found that in the process of changing from non-limit passive state to non-limit active state, the thrust of wall gradually decreases nonlinearly, and the position of the acting point of resultant force gradually increases nonlinearly, and both the change ranges are positively correlated with the internal friction angle. The theoretical formula mechanics in this paper has clear concept and convenient application, which has certain reference significance for engineers.